Does Smoking Reduce Infliximab’s Effectiveness against Crohn’s Disease? - Neeraj Narula; Richard N Fedorak (Canadian Journal of Gastroenterology)
Crohn’s disease (CD) is an idiopathic inflammatory bowel disease and has no known cure. CD symptoms are treated using an array of medicines, including biological agents such as infliximab. However, infliximab therapy is expensive; therefore, identifying variables that can help predict response to infliximab is worthwhile. The present article reviews the impact of tobacco smoking on the efficacy of infliximab in CD. Earlier studies have speculated that smoking has a negative effect on the response to infliximab in CD, but the current literature is largely unable to identify a significant relationship between the two. Although smoking is known to have a negative effect on the course of CD, as well as other organ systems, presently, a CD patient’s smoking status should not influence treatment decisions regarding infliximab therapy.